2006
DOI: 10.1111/j.1471-4159.2005.03559.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JAK/STAT signalling in neurons following spinal cord injury in mice

Abstract: The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signalling pathway is one of the most important in transducing signals from the cell surface to the nucleus in response to cytokines. In the present study, we investigated chronological alteration and cellular location of JAK1, STAT3, phosphorylated (p)-Tyr1022/1023-JAK1, p-Tyr705-STAT3, and interleukin-6 (IL-6) following spinal cord injury (SCI) in mice. Western blot analysis showed JAK1 to be significantly phosphorylated at Tyr102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 48 publications
(106 reference statements)
5
74
3
1
Order By: Relevance
“…Several studies have also indicated that Janus kinases (JAKs) and signal transducers and activators of transcription (STATs) are activated by interleukin 6 (IL6) in cardiomyocytes, macrophages, carcinoma cells and neurons and by hypoxia in pulmonary arterial smooth muscle cells, rat cardiomyocytes, retinal microvascular endothelial cells (Negoro et al, 2001;Mascareno et al, 2005;Wang et al, 2005;Dawn et al, 2004;Lee et al, 2006;Yamauchi et al, 2006;Terrell et al, 2006). STATs comprise a family of seven transcription factors that are activated by the JAK family of protein tyrosine kinases in response to stimulation by cytokines, hormones and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also indicated that Janus kinases (JAKs) and signal transducers and activators of transcription (STATs) are activated by interleukin 6 (IL6) in cardiomyocytes, macrophages, carcinoma cells and neurons and by hypoxia in pulmonary arterial smooth muscle cells, rat cardiomyocytes, retinal microvascular endothelial cells (Negoro et al, 2001;Mascareno et al, 2005;Wang et al, 2005;Dawn et al, 2004;Lee et al, 2006;Yamauchi et al, 2006;Terrell et al, 2006). STATs comprise a family of seven transcription factors that are activated by the JAK family of protein tyrosine kinases in response to stimulation by cytokines, hormones and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Yamauchi et al (104) demonstrated the peak expression of IL-6 to be consistent with the maximum activation of JAK1 and STAT3 in neurons, with translocation of phosphorylated STAT3 to the nucleus. It has previously been validated that the co-administration of IL-6 and soluble IL-6 receptor can improve neurological manifestations and protect motor neurons of the spinal cord from degeneration (105). Additional research also indicated that, compared with wild-type mice after injury, IL-6 gene knockout mice exhibited more severe damage and death of the spinal cord neurons (106).…”
Section: Astrocyte-secretory Polypeptides Promote Neuroprotection Viamentioning
confidence: 80%
“…AG490 inhibits cytokine-induced activation of JAK-2 in eosinophils stimulated with granulocyte-macrophage colony stimulating factor and selectively blocks leukemic cell growth by inducing programmed cell death (25). Related studies have suggested that AG490 also inhibits the IL-2 signaling pathway in the T cell line, d10, which fails to activate JAK-1, JAK-2, or Tyk2 (26,27). Furthermore, AG490 is an inhibitor of the JAK-2, JAK-3/STAT, JAK-3/acute protein-1 and the JAK-3/mitogen-activated protein kinase signaling pathways and potently inhibits cytokine-independent cell growth in vitro.…”
Section: Discussionmentioning
confidence: 99%